A Reliable Geocasting Solution for Underwater Acoustic Sensor Networks - B. Chen; D Pompili (Proc. of IEEE MILCOM, 2011)
Reliable data delivery for underwater acoustic sensor networks is a major concern in applications such as surveillance, data collection, navigation, and ocean monitoring. Geocasting – which is the transmission of data packet(s) to nodes located in a certain geographic region – is becoming a crucial communication primitive. In this work, two versions of a distributed, reliable, and efficient underwater geocasting protocol, which are based on different degrees of neighbor information, are proposed for underwater networks whose acoustic modems use random-access Medium Access Control (MAC) protocols. By jointly considering the position uncertainty of nodes, MAC, and routing functionalities, packet transmissions are prioritized and scheduled in order to maximize link reliability while limiting end-to-end geocasting delay. Moreover, a mechanism is designed to save the number of transmissions by selecting only a subset of neighbors for packet forwarding. Performance of the proposed protocol is evaluated and compared via simulations against existing geocasting solutions tailored for terrestrial wireless networks.